Produksi Virgin Coconut Oil Menggunakan Enzim Kasar Dari Getah Biduri (Calotropis gigantea) - Putra, I Gede Adi Darmaja; Antara, Nyoman Semadi; Suwariani , Ni Putu (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
One-of-the-most-popular-and high-value-coconut products is Virgin-Coconut-Oil (VCO). VCO products can be produced by adding proteolytic-enzymes-to optimize the release of oil from coconut milk cream. The-purpose-of this study-was to determine-the-effect of the-concentration of crude enzymes of biduri sap and incubation temperature on the properties of the-resulting VCO. Theexperimental design of this study was a two-factorial randomized group design (RAK). The concentration of enzymes as the first factor consists of four levels: 0%, 0.15%, 20%, and 0.25%, and the incubation temperature as the second factor consists of three levels: 35 oC, 40 oC, and 45 oC. The results showed that the treatment of enzyme concentration and incubation temperature had an effect on yield and water content, while (%ALB) only affected the treatment of incubation temperature and the interaction of these two factors in all treatments showed no effect. This treatment provides the best VCO characteristics at an enzyme concentration of 0.25 °C and an incubation temperature of 40 °C, with the highest yield of 42.65%, moisture content of 0.045%, %ALB 0.026%, colorless (clear), distinctive aroma of coconut oil and, the taste is quite typical of coconut oil. The resulting VCO has a very high quality because it has a higher treatment value than the SNI 7381: 2008 standard value.